2020
DOI: 10.1016/j.enpol.2019.111198
|View full text |Cite
|
Sign up to set email alerts
|

The economics of heat pumps and the (un)intended consequences of government policy

Abstract: In Europe, space and water heating account for approximately 80% of final energy use in the domestic sector. For many European countries the electrification of heat provision, via heat pumps (HPs), provides a promising decarbonisation pathway. The UK is no different, but recently concerns have been raised about the financial attractiveness of HPs given how, through various policy choices, taxes and levies are applied more heavily on electricity bills than gas bills. In this paper, we critically examine this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…They showed that GSHP may be a cost optimal solution for most of the UK in the future with increased ambient temperatures [29]. Similar results were obtained by Barnes et al [30] by comparing the net present values (NPV) of six heating systems (i.e. gas boilers, ASHP, GSHP, hybrid HP, direct electric heating and storage-based heating) in a predefined heating system that represented a typical semi-detached house.…”
Section: Literature Review Of Techno-economic Analysis Of Heatsupporting
confidence: 67%
“…They showed that GSHP may be a cost optimal solution for most of the UK in the future with increased ambient temperatures [29]. Similar results were obtained by Barnes et al [30] by comparing the net present values (NPV) of six heating systems (i.e. gas boilers, ASHP, GSHP, hybrid HP, direct electric heating and storage-based heating) in a predefined heating system that represented a typical semi-detached house.…”
Section: Literature Review Of Techno-economic Analysis Of Heatsupporting
confidence: 67%
“…Moreover, retail prices include taxes, levies, and grid charges. Not only may these mark-ups act as a disadvantage to electric heating as opposed to non-electric options (Barnes and Bhagavathy, 2020), but they also penalize thermal losses, potentially impeding an economically efficient flexible heat pump operation.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Another factor that has been shown to negatively impact the deployment of heat pumps in the UK is the current balance of tax and regulatory costs through the fuel costs, i.e. electricity and natural gas (Barnes and Bhagavathy, 2020).…”
Section: Air-and Ground-source Heat Pumpsmentioning
confidence: 99%